Self-regulated learning and motivation of Islamic studies and non-Islamic studies stream students - Mohamed Adnan, Mohamad Azrien; Mohamad, Shukeri; Buniamin, Sharifah; Mamat , Arifin (Georgian Technical University, 2014)
Self-regulated learning and motivation is important aspects of students’ learning and academic performance in a classroom context. This study aims at investigating the differences in self-regulated learning and motivation between the Islamic and non-Islamic stream students; and examining relationships between self-regulated learning, motivation and academic performance. Eight hundred and twenty five universities students were involved in this study. A self-report measure of students metacognitive self-regulation, help seeking, organization, effort regulation, self-efficacy, intrinsic and extrinsic goal orientation, task value and test anxiety was administered, and academic performance data were obtained from students’ cumulative grade point average (CGPA). The study uses a questionnaire as the information-gathering instrument. The questionnaire was based on the Motivated Strategies for Learning Questionnaire (MSLQ). T-test results indicated that students from Islamic studies background prefer using more strategies to score extrinsic goal orientation than non-Islamic studies students, and conversely, non-Islamic studies students practice metacognitive self-regulation strategies and organization strategies more than Islamic studies students did. Correlation analysis revealed that self-efficacy, intrinsic and extrinsic goal orientation, task value and test anxiety were positively related to metacognitive self-regulation, help seeking and organization. Regression analyses showed that test anxiety and intrinsic goal orientation appeared as the best predictors of academic performance.